Self-sufficiency ratio: an insufficient metric for domestic PV-battery systems?. (October 2018) - Sun, S.I.; Kiaee, M.; Norman, S.; Wills, R.G.A.
Abstract: By installing a home battery to accompany rooftop solar PV, grid electricity usage is reduced and self-sufficiency increased. One motivation for pursuing this goal is environmental concern. By modelling domestic PV-battery systems in this work, self-sufficiency is found not to correlate well with CO2 emissions savings, in some cases even correlating negatively. A system's complexities, such as transmission and distribution losses, are not encapsulated in self-sufficiency. Self-sufficiency should not be considered in isolation when designing PV-battery systems to maximize CO2 emissions savings.